DUKUNGAN RUMAH PONDOKAN MAHASISWA TERHADAP PROSES BELAJAR MAHASISWA FAKULTAS TEKNIK UNY - Bambang Sugestiyadi (Universitas Negeri Yogyakarta, 2006)
This research is a preliminary study on the role of the student dormitory tosupport the study process of engineering students of Yogyakarta State University.The research is aimed to reveal the relationship between student dormitoryareas and the study process of the engineering students in the YogyakartaState University. The support on the study process of the engineering studentsare the non-physical support such as the dormitory area and the physicalsupport such as the facilities of the dormitory.The nature of the research is a qualitative research. The engineering studentsof the Yogyakarta State University and their dormitory were decided as the respondent.11 dormitory students were selected as the samples. The questionerthat was used for a cross check field observation are collected randomly from50 (fifty) engineering faculty students of the Yogyakarta State University.The result of the research clarifies that there are 81.81 % of respondentslived in a permanent dormitory building. The construction of dormitory consist87..87% of one floor building. The research also shows that the spatialoccupancy of the dormitory is 7.50 up to 9.00 meter square per person. Thiscondition has already fulfilled the minimum requirement that is 6.00 metersquare per person. It indicates that the dormitories support the student liveexternally and internally. 93.90% respondents clarify that the dormitory hasalready became the place for study as well as for live. 78.75% respondentsclarify that the dormitory area is sufficient to support the process of study.Key words: student dormitory, facility, studying support ability